Assessment of the Sustainable Management of Tourism Destinations in a Chartered City - Cea, Abraham; Denuevo, Althea (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to assess the sustainable management of tourism destinations in terms of planning, leading, organizing, and controlling in a Chartered City. This study used a quantitative method focusing on a descriptive-correlational method, with 200 participants in the study, consisting of four types: the government sector, business sector, community, and tourists. The evaluation on the sustainable management practices employed in tourism destinations, specifically through the lenses of planning, leading, organizing, and controlling not only considered the entire group of implementers but also classified them based on their demographic profiles, such as age, sex, civil status, educational background, participant classification, income level, and years of service shown the positive relationship between the characteristics of the implementers and the sustainability of tourism management practices. The analysis revealed how different demographic factors influenced the sustainability of the management practices. It provided insights into areas where improvements can be made to ensure that all stakeholders are effectively engaged in the tourism management process. There were significant differences in sustainable management of the tourism destinations regarding PLOC when classified according to age, sex, civil status, highest educational attainment, participant’s classification, average monthly income, and number of years in service. Also, significant relationships exist among the implementers’ profiles in terms of age, sex, civil status, highest educational attainment, participants’ classification, average monthly income, and number of years in service, and the sustainable management of the tourism destinations in terms of PLOC. To conclude, the study highlighted the importance of sustainability in tourism destinations, particularly within Chartered Cities. It was recommended that training and development programs be conducted to address the growing demand for sustainable management practices in tourism.